2016
DOI: 10.4111/icu.2016.57.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nutritional intake assessment in patients with urolithiasis: A decision impact analysis

Abstract: PurposeTo evaluate a physician's impression of a urinary stone patient's dietary intake and whether it was dependent on the medium through which the nutritional data were obtained. Furthermore, we sought to determine if using an electronic food frequency questionnaire (FFQ) impacted dietary recommendations for these patients.Materials and MethodsSeventy-six patients attended the Stone Clinic over a period of 6 weeks. Seventy-five gave consent for enrollment in our study. Patients completed an office-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Men are more prone to experienced urolithiasis in comparison to women as commonly reported in several studies [6][7][8]15,18]. The results from previous studies showed that the prevalence of urinary stone was higher in male than in female by the ratio of 2:1 [7,8].…”
Section: Gendermentioning
confidence: 79%
See 4 more Smart Citations
“…Men are more prone to experienced urolithiasis in comparison to women as commonly reported in several studies [6][7][8]15,18]. The results from previous studies showed that the prevalence of urinary stone was higher in male than in female by the ratio of 2:1 [7,8].…”
Section: Gendermentioning
confidence: 79%
“…Eating habit was the main factors contributing towards the formation of stones in the urinary tract. Various studies have shown a link between high animal protein diets and increased incidence of kidney disease [7,15,18]. Thus, it was recommended to adopt an animal-free vegetarian diet which lower the risk of urolithiasis [7,15,18].…”
Section: Dietary Practice and Lifestyle Behaviourmentioning
confidence: 99%
See 3 more Smart Citations